Numerical Study on Noise Reduction of Gas Extinguishing Nozzle Using Adsorbent - Sun Kim, Hak; Hwan Kim, Yo; Ju Hwang, In; jea Kim, Youn (International Journal of Engineering and Technology, 2018)
Currently, gas-based firefighting systems tend to release fire extinguishing agent at pressures of around 100 bar or more for quick firefighting. The flow noise produced by the agent discharge is approximately 140 dB, which is similar to fireworks. This powerful sound pressure level (SPL) results in equipment failure during the fire suppression process, accelerating the movement studies to reduce flow noise. Most previous studies have selected design parameters such as packing density, porosity, and absorbent arrays, but these factors alone do not address noise reduction issues. The methods used in this study constitute the thickness of the absorber in the nozzle. The sound absorber plays an important role in absorbing sound pressure by flow noise depending on its shape. In this study, numerical analysis was performed using ANSYS CFX ver. 18.1 to investigate the characteristics of flow noise and sound absorption. The thickness of the absorber shall be reduced or increased by 1 mm in relation to 86 mm. In particular, if the absorber diameter increases by 2 mm in the newly designed model, SPL is shown at 121.55 dB, down 9.3 % from the reference model.Â Â